The church systems of England in the nineteenth century the sixth congregational union lecture - Rogers, James Guinness, 1822-1911 (London, UK Hodder and Stoughton, 1881)
Contents includes : Lecture X : the Plymouth Brethren (pages483-534). Includes index
Donated by Dr L.L. Edwards.
Keywords: Brethren movement -- criticism; Great Britain -- church history -- 19th century